CONCEPT OF CONSTRUCTION OF POWER CIRCUITS OF A MULTILEVEL MODULAR CONVERTER AND ITS TRANSISTOR MODULES - George G. Zhemerov (Електротехніка і електромеханіка, 2018)
Goal. The goal of the paper is to study the peculiarities of building power circuits of a modular multilevel converter (MMC) of electrical energy for DC transmission lines, to investigate its operating principles and basic characteristics. Methodology. We have applied the theory of electrical circuits and mathematical simulation in Matlab package. Results. A Matlab-model of the MMC power circuit was constructed with shunting of all the shoulders by current sources, which made it possible to check the correctness of the formulas for the characteristics of the proposed circuits. Originality. Variants of power circuits of MMC with shunting of all shoulders of the converter by current sources are offered. The tables of states of HB and FB modules for forward and backward direction of the current of the shoulders are made. Practical value. The use of the proposed structure of the converter power circuit and the algorithms of operation of the power transistor modules will help to determine the scope of their application, will help in the synthesis of the control system and analysis of possible emergency modes of the MMC.